Cluster Preface: Modern Nickel-Catalyzed Reactions - Martin, Ruben; Molander, Gary A. (Synlett, 2021)
Ruben Martin is a professor at the Institute of Chemical Research of Catalonia (ICIQ), Tarragona, Spain. He received his Ph.D. in 2003 from the University of Barcelona under the guidance of Prof. Antoni Riera. In 2004, he moved to the Max-Planck Institut für Kohlenforschung as a Humboldt postdoctoral fellow with Prof. Alois Fürstner. In 2005, he undertook further postdoctoral studies at MIT with Prof. Stephen L. Buchwald as a MEC-Fulbright fellow. In 2008, he began his independent career as an assistant professor at the ICIQ (Tarragona). In 2013, he was promoted to associate professor and shortly after to ICREA Research Professor. Ruben Martin has focused his career on designing synthetically useful Ni-catalyzed methodologies for streamlining the preparation of added-value chemicals from simple precursors without losing sight of mechanistic considerations, when appropriate.Gary A. Molander is a professor at the University of Pennsylvania, Philadelphia, United States. He completed his undergraduate studies in chemistry at Iowa State University under the tutelage of Prof. Richard C. Larock. He earned his Ph.D. at Purdue University under the direction of Prof. Herbert Brown and undertook postdoctoral training with Prof. Barry Trost at the University of Wisconsin, Madison. He began his academic career at the University of Colorado, Boulder, moving to the University of Pennsylvania in 1999, where he is currently Professor of Chemistry. His research interests have focused on the utilization of organolanthanides, Pd-catalyzed cross-coupling reactions with trifluoroborate salts, and the merger of photoredox catalysis and Ni catalysis for tackling a priori uphill transformations under visible-light irradiation for accessing valuable scaffolds in both academic and pharmaceutical laboratories.